ANALISIS UPAYA PENGUATAN IMPLEMENTASI KEBIJAKAN NETRALITAS ASN DALAM PEMILU 2024: ANALISIS UPAYA PENGUATAN IMPLEMENTASI KEBIJAKAN NETRALITAS ASN DALAM PEMILU 2024 - Hasanah, Ade uswatun (Lentera Ilmu Madani, 2024)
The General Election People's Festival which occurs every 5 years is something to look forward to because the election process is quite long so that fraud often occurs such as neutrality violations committed by ASNs. Various efforts are always made in every election. The ASN Neutrality Law is regulated in ASN Law no. 5 of 2014 which states that every ASN does not take sides from any form of influence and does not take sides in anyone's interests. It is stated that the influence in question is the influence of political parties. Prior to the issuance of this Law, the Government of the Republic of Indonesia issued Regulation Number 53 of 2010 which stated regarding Civil Servant Discipline. In this regulation, it is interpreted that what is meant by Civil Servant Discipline is the ability of Civil Servants to comply with obligations and avoid prohibitions specified in statutory regulations and/or official regulations. If they are not obeyed or violated, they will be subject to disciplinary punishment. Disciplinary violations in question are any words, writings or actions of civil servants that do not comply with obligations and/or violate prohibitions on civil servant disciplinary provisions, whether committed inside or outside working hours. PP Number 53 of 2010 is still realistic and in line with the realities of the current political season so it is still used as a basic reference for ASN integrity. Even though the word neutrality is not written concretely in the PP, article 4 points 12 and 13 prohibit every civil servant from engaging in practical politics or providing support to candidates in elections. Based on this, there is a need for an Implementation analysis so that there are efforts to strengthen the Implementation of the ASN Neutrality Policy in the 2024 Election with the Merilee S. Grindle Implementation Model. Where policy implementation is seen from 2 variables, namely the policy context variable (context of policy). The content variables are closely related to interests, goals to be achieved, resources that can be provided and the background of the factors involved in implementing the policy. Meanwhile, context variables relate to the environment in which policies are made and administrative activities are carried out. Keywords: Implementation of Public Policu, Netrality, Civil Governance, Election